Quality of life of hemodialysis patients waiting for kidney transplant - Dedić, Gordana; Milojković, Nenad; Čukić, Zoran; Bokonjić, Dubravko (Vojnosanitetski pregled, 2017)
Background/Aim. Dialysis and kidney transplantation are treatments that can be applied to patients with the end-stage renal disease. There is a lack of information on the quality of life (QOL) among hemodialysis (HD) patients on the waiting list for a kidney transplant, a group that is increasing all over the world. The aim of this study was to investigate the quality of life of patients on HD waiting for a kidney transplant. Methods. In the clinical comparative 12-month study, QOL level was compared between consecutively recruited patients waiting for a kidney transplant (WT patients) (N = 24) and patients not waiting for a kidney transplant (non-WT patients) (N = 52). All patients were older than 18 years and were on HD at least three months. To measure QOL, the short Form Health Survey (SD-36) was used. Results. WT patients were younger (43.50 ± 12.64 vs 63.58 ± 13.88 years; p < 0.001), they had started dialysis in the younger age (32.38 ± 14.50 vs 57.12 ± 15.79 years; p < 0.001) and spent more time on dialysis (112.04 ± 82.48 vs 72.40 ± 81.31 months; p < 0.05) than non-WT patients. Non-WT patients had more comorbidities than WT patients (p < 0.01). In laboratory parameters, there were statistically significant differences in values of serum creatinine (p < 0.01), phosphorus (p < 0.05) and number used to quantyfy hemodialysis treatment adequacy (Kt/V index: K – dialyzer clearance of urea; t – dialysis time; V – volume of distribution of urea approx equal to patients’ total body water) (p < 0.05). Mean scores were higher among WT patients compared to non-WT patients in four dimensions of QOL: Physical Function (PF) (83.33 ± 10.59 vs 66.53 ± 27.87; respectively p > 0.05), Role Physical (RP) (58.66 ± 21.39 vs 46.90 ± 23.73; respectively p > 0.05), General health (GH) (45.00 ± 14.81 vs 37.98 ± 12.88; respectively p > 0.05); Social Functioning (SF) (93.66 ± 16.10 vs 78.30 ± 29.80; respectively p > 0.05) including Physical Component Summary (PCS) scores (64.16 ± 13.77 vs 52.38 ± 19.53; respectively p > 0.05). Conclusion. Patients waiting for a kidney transplant were younger, had started dialysis in the younger age and spent longer on dialysis compared with patients not eligible for transplantation. Low comorbidity, better laboratory parameters interferes in all domains with higher values of QOL in patients waiting for a kidney transplant, especially in general health, physical conditions and social functioning.
Keywords: renal dialysis; kidney transplantation; quality of life; surveys and questionnaires